Expressions of the use of slang among millennial youth on social media and its impact of the extension of Indonesia in society - Dedi Saputra; Vismaia S Damayanti; Yeti Mulyati; Wahyudi Rahmat (BAHASTRA, 2023)
The research was conducted because of the widespread use of slang among the Indonesian population, especially millennial youth. This study also aims to examine millennial youth slang based on its form, source and pattern of formation, purpose and context of use. The research approach used is descriptive qualitative, namely examining language data in the form of the use of slang by millennial youth and interpreting it. Sources of research data are interview results and social media, namely Facebook, Twitter and Instagram, which contain teenage slang. Data collection techniques were documented, observed and recorded, as well as interviews with fifteen young people who used slang in communicating. The data analysis technique in this study is content analysis. The results of the study show that the use of slang by millennial youth originates from regional languages, Indonesian, foreign languages, as well as a combination of Indonesian and foreign languages. The pattern of forming slang from abbreviations, shortening of words, acronyms, reversal of words, spoofed words and shifts in meaning. The expression of the use of slang among millennial youth on social media and its impact on the extension of Indonesian in society makes a big change in the world of language, this is because teenagers are contaminated by foreign languages so this has an impact on the extension of society. Regarding this problem so that ordinary people feel accustomed to and contaminated with the slang that is widely used by millennial youth at this time, this will affect the resilience of the Indonesian national language which is the identity of the country, so that the impact begins to fade the use of good Indonesian and true because it has been contaminated with the influence of foreign languages.